2009
DOI: 10.1007/s00467-008-1018-4
|View full text |Cite
|
Sign up to set email alerts
|

Timing of voiding cystourethrography in infants with first time urinary infection

Abstract: The aim of the study was to evaluate whether the timing of performing a voiding cystourethrography (VCUG) following a first urinary tract infection (UTI) in infants is related to the presence or the severity of vesicoureteral reflux (VUR). A total of 411 children (male 230, female 181) with a first-recognised UTI between ages 15 days and 12 months (median 3 months) underwent a VCUG within 4-81 days (median 9 days) following diagnosis. The presence and the grade of the VUR were compared in two groups: an "early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 21 publications
1
6
0
2
Order By: Relevance
“…Mahant et al revealed that timing of VCUG did not influence the prevalence and severity of reflux during the first week and later ( 7 ). Results of other studies were in accordance with report of Mahant et al They recommended that VCUG should be conducted as soon as possible ( 6 , 10 - 13 ). Previous authors believes that VCUG should be done at the end of treatment, when discharging the patient from hospital ( 1 ).…”
Section: Discussionsupporting
confidence: 87%
“…Mahant et al revealed that timing of VCUG did not influence the prevalence and severity of reflux during the first week and later ( 7 ). Results of other studies were in accordance with report of Mahant et al They recommended that VCUG should be conducted as soon as possible ( 6 , 10 - 13 ). Previous authors believes that VCUG should be done at the end of treatment, when discharging the patient from hospital ( 1 ).…”
Section: Discussionsupporting
confidence: 87%
“…Cystourethrography (VCUG) remains the gold standard, permitting an exact grading according to the International Working Group on VUR in children (52), but because of its higher radiating dose, it should be limited to selected patients (in particular, to males in whom there is a suspicion of posterior urethral valves). The timing of cystourethrography can be established according to local organization and to family convenience, as there is evidence that neither the presence nor the grade of VUR is influenced by the timing of the examination following diagnosis of UTI (53–55) [grade B].…”
Section: When Should An Ultrasound Be Performed?mentioning
confidence: 99%
“…The detected pathogens included: Escherichia coli, Proteus species, Pseudomonas aeruginosa, Staphylococcus species and Klebsiella pneumoniae . The examinations were performed no sooner than 2 weeks after the last urinary tract infection had been treated ( 7 ) .…”
Section: Methodsmentioning
confidence: 99%